Pengaruh PENGARUH KONSENTRASI HIDROGEN PEROKSIDA (H202) 3% TERHADAP PERTUMBUHAN DAN HASIL BERBAGAI VARIETAS SELADA PADA SISTEM HIDROPONIK NFT - Aditya Nur Fauzie; Nurlaila Fatmawati (Journal of Horticulture Production Technology, 2026)
The limited domestic supply of lettuce has been unable to meet the increasing market demand. This study aimed to evaluate the effect of a 3% hydrogen peroxide (H₂O₂) concentration on the growth and yield of various lettuce varieties NFT hydroponic system. The experiment was conducted from December 2025 to January 2026 in Madukara, Banjarnegara, using a Completely Randomized Design (CRD) consisting of three lettuce varieties with nine replications. Data were analyzed using JASP software, followed by Tukey's Honestly Significant Difference(HSD) test at the 5% significance level. The results showed that the application of a 3% H₂O₂ concentration had a significant effect (P < 0.05) on all measured parameters. The Romaine variety (V1) consistently showed superior performance in plant height, number of leaves, stem diameter, root length, and produced the highest fresh weight(174.5 g) and dry weight (15.67 g). Meanwhile, the Butterhead variety (V3) recorded the greatest leaf width (91.61 mm). These findings indicate that the oxygen supplied by the 3% H₂O₂ concentration effectively enhanced root metabolism; however, overall productivity was largely determined by the genetic potential of each variety, with Romaine exhibiting the highest adaptability. Therefore, the application of a 3% H₂O₂ concentration in an NFThydroponic system can be recommended as an effective strategy to optimize commercial lettuce production, particularly for the Romaine variety.